Investigating the Influence of Attitude, Prior Knowledge, and Critical Thinking on Solving Algebraic Equations - Adoro, Jona Belle; Dulay, Ednalyn; Talenjale, Miguel; Balanquit, Cherry; Nobis, Martin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study looks into how students' abilities to solve algebraic problems are impacted by their attitude, past knowledge, and critical thinking. Despite being a fundamental mathematical skill, many students find it difficult to solve algebraic problems. A descriptive-correlational methodology was used in this study to assess respondents' performance as well as the factors that affect respondents' ability to solve algebraic equations and how those factors relate to respondents' performance. Although several students scored extremely low on equation-solving tests, the statistical analysis showed no discernible relationship between the components (critical thinking, attitude, and prior knowledge) and overall performance. These results point to the need for more research into the variables that can affect how well pupils solve algebraic equations.